Eye-see:ai-developed device for the visually impaired - Ishak, Mohamad Hafis Izran (Penerbit UTHM, 2022)
In the 21st century, the need for the visually impaired to have a technologically controlled vision to assist in their daily life, is a necessity. Therefore, in this work, utilizing Artificial Intelligence (AI) technology, a software is developed to help the visually impaired to see the world better through the lens of the creation. The developed software is created to help the visually impaired lead a better daily life, hence they will not stumble upon obstacles anymore. The work involves the use of AI, controller, sensor, voiceover, and python programming. The sensors are utilized to monitor any obstacles in the path of the visually impaired, senses the obstacle and then send signals to the controller. The installed animated voice will then redirect the path by identifying the location of the obstacle, hence the visually impaired will be able to avoid the obstacle altogether. Visual impairment can limit an individual's ability to perform simple daily tasks with independence. Hence, with a successful implementation of the system will improve the quality of life of the visually impaired, tremendously. Globally, a total of 1 billion people suffer from visual impairment (moderate or severe distance impairment or blindness) which could have been prevented or is yet to be addressed.